Estudo prospectivo randomizado em mulheres com bexiga hiperativa tratadas com neuromodulação transcutânea sacral, acupuntura ou solifenacim - Perez, Maria Graciela Varela [UNIFESP] (2016)
Aim: To evaluate the effectiveness of transcutaneous neuromodulation sacral, acupuncture or solifenacin in women with overactive bladder symptoms Casuistry and Methods: In a randomized, prospective and longitudinal trial were compared three groups: group A (transcutaneous neuromodulation sacral), group B (acupuncture) and group C (medication). They were assessed the quality of life responding the questionnaires King?s, Iqol, Iciq, V8, Fsfi and Qsf, and urinary symptoms through the voiding diary for seven days and pad test. The patients of group A received, twice a week, during twelve consecutive weeks, transcutaneous neuromodulation sacral using Tens current (transcutaneous electric nerve stimulation) through transcutaneous electrode stickers placed on both sides of the sacral vertebrae in level S2 and S4. The parameters of the current were: frequency of 10 Hz, pulse length of 200 microseconds and current intensity according to the tolerance of each patient. The patients of group B received, once a week, during twelve consecutive weeks, acupuncture, and they were used sterile and single-use needles during 20 minutes. The patients of group C received solifenacin (5mg) medication daily, provided by the medical service, with monthly control for twelve consecutive weeks. The three groups were reevaluated after twelve weeks of treatment. Results: They were included 23 patients in group A, 20 patients in group B and 8 patients in group C. After the treatment, the group A showed a significant reduction of urgency, urge-incontinence, nocturia and number of pads required; the group B reduced significantly urgency, urge-incontinence, nocturia and loss of urine (in gramme) in the pad test and the group C reduced significantly nocturia. There was no significant statistical difference between the three groups in the evaluation of these variables after treatment. There were significant improvements in the quality of life in the three groups, and there was only an intergroup difference between the groups C and B in the domain ?measurement of gravity? of the King?s questionnaire , with best results in the first group. Conclusion: Based on our results we can conclude that transcutaneous neuromodulation sacral, acupuncture and solifenacin (5mg) were effective in alleviating the symptoms of overactive bladder improving the polyuria, urgency, urge-incontinence, nocturia, urinary incontinence and quality of life after twelve weeks of treatment; where medication had more efficacy than acupuncture in the analysis of the item ?measurement of gravity? of the King?s questionnaire of quality of life.